Behaviors of partially concrete-filled welded integral T-joints in steel truss bridges. (1st July 2018) - Cheng, Bin; Xiang, Sheng; Zuo, Wei; Teng, Nianguan
Highlights: We carried out static tests of partially concrete-filled welded integral T-joints in steel truss bridges. We established refined FE models for elasto-plastic analysis of partially concrete-filled welded integral T-joints. We investigated the influences of concrete filling length on structural behaviors. We proposed the optimal concrete filling range for partially concrete-filled welded integral T-joints. Abstract: This research focuses on the structural behaviors of partially concrete-filled welded integral T-joints in steel truss bridges. The T-shape integral joints, which are composed of welded box-section members, were simply supported at chord ends so that the loading cases of horizontal force and vertical force at brace end can be considered. Static tests are first conducted for six specimens, of which three are with arc transitions at chord-to-brace corners and the other three are without arc transitions. Three cases of concrete filling in chord, i.e., hollow chord, partial concrete filling in chord, and full concrete filling in chord, were considered. The elastic and elasto-plastic behaviors including rigidities, steel strains at critical locations, failure modes, characteristic loads, and characteristic deflections of the joints were obtained. The effects of internal concrete were comparatively analyzed. Finite element models were also developed to predict the load bearing capacities of joints by considering various concrete filling ranges in the chord. The numerical outputs were validated by the test results. The influences of concrete filling length on structural behaviors including elastic rigidity, yield load, and ultimate load were revealed on the basis of numerous parametric studies. Both experimental and numerical results indicate that the joints whose chords have been partially filled with concrete are expected to provide the structural behaviors as good as those of fully concreted-filled joints, both of which are obviously higher than those of hollow joints (i.e., without concrete filling in chord). The optimal concrete filling lengths in the chord of welded integral joints are suggested to be three times the chord's sectional height by considering both beneficial and adverse effects of internal concrete.